2006
DOI: 10.1177/154193120605000341
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Crossmodal Links in Attention for the Design of Multimodal Interfaces: A Driving Simulation Study

Abstract: The design of multimodal interfaces rarely takes into consideration recent data suggesting the existence of considerable crossmodal spatial and temporal links in attention. This can be partly explained by the fact that crossmodal links have been studied almost exclusively in spartan laboratory settings with simple cues and tasks. As a result, it is not clear whether they scale to more complex settings. To examine this question, participants in this experiment drove a simulated military vehicle and were periodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…Our results also argue against simple accounts of the modality‐specific nature of attentional resources 73–76 . However, these findings are not only of theoretical interest, they are also of profound applied relevance, given the growing interest in using nonvisual (and multisensory) cues to alert interface operators’ whose visual attention might otherwise be overloaded to signs of impending danger 77–80 …”
Section: On the Automaticity Of Crossmodal Cuing Effectsmentioning
confidence: 57%
“…Our results also argue against simple accounts of the modality‐specific nature of attentional resources 73–76 . However, these findings are not only of theoretical interest, they are also of profound applied relevance, given the growing interest in using nonvisual (and multisensory) cues to alert interface operators’ whose visual attention might otherwise be overloaded to signs of impending danger 77–80 …”
Section: On the Automaticity Of Crossmodal Cuing Effectsmentioning
confidence: 57%
“…More research is necessary to determine the most effective placement, presentation, number, and intensity of a tactile display for rear-end collision warnings. Regardless of driver preference, the present findings, along with previous research (e.g., Lee, Hoffman, & Hayes, 2004;Ferris, Penfold, Hameed, & Sarter, 2006), support tactile warnings over visual and audio warnings for rear-end collision avoidance-some drivers may not have preferred the tactile warnings, but they worked the best to improve brake RT! Interestingly, there is a near-even split between drivers that prefer visual warnings and those that prefer tactile warnings.…”
Section: Driver Preferencesmentioning
confidence: 57%
“…acoustic, visual and haptic within concept E) caused an interrelated conflict. Ferris, Penfold, Hameed, and Sarter (2006) revealed that invalid cross-modal cues (e.g. a driver perceives an auditory cue to come from a different location than a visual cue although both are meant to indicate the same target) lead to longer response times and reduce response accuracy.…”
Section: Figure 7-7 Percentages Correct Situation Awareness (Based Onmentioning
confidence: 99%
“…The acoustic warning did not provide spatial cues either. According to Ferris et al (2006) weak cross-modal links could already negatively influence performance. Therefore, weak crossmodal links of concept E could be an explanation for reduced reaction times.…”
Section: Figure 7-7 Percentages Correct Situation Awareness (Based Onmentioning
confidence: 99%
See 1 more Smart Citation